Competitividade e danos de cordas-de-viola em soja - Piccinini, Fernando (2015)
The weeds adversely interfere with the development, yield and quality of soybean [Glycine max (L.) Merr.]. The inappropriate use of herbicides for weed control can lead to resistant biotypes appearance or tolerant, causing a change in the flora of weeds in fields. An example of this is the increased occurrence of morning-glory (Ipomoea spp.) In the fields of southern Brazil. The aim of this study were (i) to investigate the competitive ability of soybean and I. triloba, I. purpurea and I. indivisa undivided through the experimental method of substitutive series. (ii) quantify the losses arising from the competition of two species of morning-glory in coexistence with soybean. We conducted two experiments at greenhouse in a completely randomized design with four replications, using pots with a 8 dm3 capacity, with ratios of soybean and morning-glory 100: 0, 75:25, 50:50, 25:75 to 100: 0, the population was defined in the preliminary experiment 250 plants m-2. The second study was conducted in the field in the season 2013/2014. The experimental design was a randomized block design with four replications, with treatments being distributed in a factorial sequence, which evaluated the effect of competition on two soybean cultivars (TEC6029 and TEC7849), of a morning-glory (I . triloba and I. purpurea) infestation in different densities (0, 4, 8, 16 and 32 plants m-2). In the first experiment, the observed deviations in relative yield and straight overall relative yield in relation to the expected lines, resulted in convex lines for soybeans and concave to Ipomoea spp, so there was competition for resources and a more competitive species than the other. Soybean showed competitiveness more than morning-glory when species were in the same proportion. In the second experiment the soybean field coexistence with different population of morning-glory affects yield components and grain yield.